If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-2)=9-2x
We move all terms to the left:
3(-2)-(9-2x)=0
We add all the numbers together, and all the variables
-(-2x+9)+3(-2)=0
We add all the numbers together, and all the variables
-(-2x+9)-6=0
We get rid of parentheses
2x-9-6=0
We add all the numbers together, and all the variables
2x-15=0
We move all terms containing x to the left, all other terms to the right
2x=15
x=15/2
x=7+1/2
| 6+8d=24 | | X^2=3y+y | | 2x/7=3.5 | | 4x=-16-12x | | -210+110x-6x^2=0 | | 2y➕4=16 | | x-2/14=3/7 | | 3(2x+1)-2(3x+1)=0 | | 1=-9-x | | 4-12a=20 | | 3x=-9+12x | | 8x-14=3x+46 | | -3x^2+6-3x=0 | | 2x=13-11x | | 5x-(x+2)=37 | | x-4/14=6/7 | | 1/8+c=4/8 | | 9h-3=6 | | 5x+16=−2x−19 | | x^2-45x+1000=0 | | H(t)=-16t²+6 | | 6=y+20 | | 3.14÷x2-36=8 | | y/9+10=5 | | (2w-3)÷6=4 | | 7x-8=5x-4 | | X-2=7x-8 | | 3/13x+1/3=2/5-10/13x+2/5 | | 7p+2=5p+8p= | | 7x9=-75-4x | | x+14+6x-4=180 | | 2x+10+2x-8÷2=25 |